Circulating Annexin A5 Levels after Atrial Switch for Transposition of the Great Arteries: Relationship with Ventricular Deformation and Geometry - Lai, Clare T. M. (Public Library of Science, 2012)
BACKGROUND: Inflammatory cytokines, cardiomyocyte apoptosis, and altered collagen turnover may contribute to unfavourable ventricular remodeling. This unfavourable ventricular remodelling is well documented in patients after atrial switch operation for complete transposition of the great arteries. We therefore tested if levels of circulating markers of inflammation, apoptosis, collagen synthesis, and extracellular matrix degradation are altered in patients after atrial switch operation for transposition of the great arteries. METHODS AND RESULTS: Circulating tumour necrosis factor (TNF)-α, annexin A5 (AnxA5), carboxy-terminal propeptide of type I procollagen (PICP), amino-terminal propeptide of type III procollagen (PIIINP), matrix metalloproteinase-1 (MMP-1), and tissue inhibitor of metalloproteinase-1 (TIMP-1) levels were determined in 27 patients aged 25.2±3.1 years and 20 controls. Ventricular myocardial deformation and left ventricular eccentricity index (EI) were determined by speckle tracking and two-dimensional echocardiography, respectively. Compared with controls, patients had significantly higher circulating AnxA5 (p<0.001) and TNF-α (p = 0.018) levels, but similar PICP, PIIINP, MMP-1 and TIMP-1 levels. For the whole cohort, plasma AnxA5 correlated with serum TNF-α (p = 0.002), systemic ventricular global longitudinal strain (GLS) and systolic and early diastolic strain rate (all p<0.001), and subpulmonary ventricular GLS and early diastolic strain rate (both p<0.001). In patients, plasma AnxA5 level correlated positively with subpulmonary ventricular EI (p = 0.027). Multiple linear regression analysis identified systemic ventricular GLS (β = −0.50, p<0.001) and serum TNF-α (β = 0.29, p = 0.022) as significant correlates of plasma AnxA5. CONCLUSIONS: Elevated plasma AnxA5 level in patients after atrial switch operation is associated with impaired systemic myocardial deformation, increased subpulmonary ventricular eccentricity, and increased serum TNF-α level.